2005
DOI: 10.1074/jbc.m502852200
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of the Lipopolysaccharide Outer Core Affects Susceptibility to Antimicrobial Peptides and Virulence of Actinobacillus pleuropneumoniae Serotype 1

Abstract: We reported previously that the core oligosaccharide region of the lipopolysaccharide (LPS) is essential for optimal adhesion of Actinobacillus pleuropneumoniae, an important swine pathogen, to respiratory tract cells. Rough LPS and core LPS mutants of A. pleuropneumoniae serotype 1 were generated by using a mini-Tn10 transposon mutagenesis system. Here we performed a structural analysis of the oligosaccharide region of three core LPS mutants that still produce the same O-antigen by using methylation analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 41 publications
(37 reference statements)
4
46
1
Order By: Relevance
“…We now demonstrated that LOS significantly impaired the adhesion of H. parasuis to PBMEC, suggesting a role for this bacterial component as an adhesin. Likewise, LPS from other bacterial species, including swine pathogens of the same family, such as Actinobacillus pleuropneumoniae have been shown to be important adhesins [30,32]. Nevertheless, other adhesins may also contribute to bacteria-cell interactions based on our finding that the addition of LOS to a competitive assay did not completely abolish the adhesion of H. parasuis to PBMEC.…”
Section: Discussionmentioning
confidence: 40%
“…We now demonstrated that LOS significantly impaired the adhesion of H. parasuis to PBMEC, suggesting a role for this bacterial component as an adhesin. Likewise, LPS from other bacterial species, including swine pathogens of the same family, such as Actinobacillus pleuropneumoniae have been shown to be important adhesins [30,32]. Nevertheless, other adhesins may also contribute to bacteria-cell interactions based on our finding that the addition of LOS to a competitive assay did not completely abolish the adhesion of H. parasuis to PBMEC.…”
Section: Discussionmentioning
confidence: 40%
“…Additional mutant strains must be constructed in order to test the importance of LPS outer core sugars for antimicrobial peptide resistance. In other organisms, such as Y. enterocolitica and Actinobacillus pleuropneumoniae, the outer core residues contribute to antimicrobial peptide resistance (45,50). SAL1 does not survive in the rat agar bead model of chronic lung infection.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial peptides are a critical component of the innate immune system of higher organisms (18). A (21,25). We have shown recently that the terminal PCho residues on the P. multocida LPS contribute to resistance to fowlicidin 1 (14).…”
Section: Resultsmentioning
confidence: 99%